Typological Analysis of Digital Indo-Arabic Research Terms Dictionary with a Lexicographical Approach - Firman Nurul Fauzi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Today, printed dictionaries are less attractive to their users. Even though dictionaries are significant in learning languages, especially foreign ones, technological developments have led to the emergence of dictionaries in digital form with various conveniences. This study aims to: 1) find out the typology of digital ”Kamus Istilah Penelitian Indo-Arab” based on a lexicographical approach, 2) find out the ideal criteria contained in the ”Kamus Istilah Penelitian Indo-Arab.” The data collection technique used in this article is library documentation with the dictionary application as the source. The results of this article are: 1) ”Kamus Istilah Penelitian Indo-Arab” is included in the typology of bilingual or bilingual dictionaries, special dictionaries, alphabetical dictionaries, and limited thematic dictionaries. 2) this dictionary meets the criteria of an ideal dictionary, namely completeness, brevity, accuracy, and ease of explanation.